Preparation and Cu(II) ion removal capacities of Schiff base-based polystyrene nanocomposites for wastewater treatment. Issue 197 (24th March 2019) - Zhang, Lexin; Feng, Yao; Zhang, Lun; Zhou, Jingxin; Zhang, Qingrui; Jiao, Tifeng
Abstract: In this paper, new composite nanomaterials by encapsulating Schiff base molecules with hydrophilic spacers into sulfonate groups charged polystyrene beads (PS) have been prepared. The obtained composite adsorbent, Schiff base-based polystyrene nanocomposites (PS-GN1), demonstrated more preferable Cu(II) ion removal capacity in the presence of Ca 2+ co-ions in solutions. And the obtained PS-GN1 composites with inner well-dispersed Schiff base molecules demonstrated much faster breakthrough for Cu(II) ion removal than PS beads mainly due to the electrostatic forces and coordinating reaction with Cu(II) ion. The present research work showed it potential to prepare excellent nanocomposites for the removal of toxic metal ions and other charged pollutants from wastewater.